THE PRINCIPAL'S LEADERSHIP BEHAVIOR IN MOTIVATING TEACHERS (CASE STUDY OF SMP PGRI SUNGGUMINASA) (International Conference on Social and Islamic Studies, 2022)
The leadership behavior displayed by a leader is very necessary in moving his subordinates to achieve organizational / agency goals. The principal as the leader of an educational institution not only plays an important role in driving school management, but plays a role in motivating teachers as an impetus for them to behave. This article aims to describe the principal's leadership behavior in motivating teachers to teach at SMP PGRI Sungguminasa. Research is a qualitative research type of case study research conducted at SMP PGRI Sungguminasa. The source of the data comes from the principal and teacher representatives. Data collection in this study used interviews and observations. Data analysis using descriptive analysis. The results showed that the principal's behavior in motivating teachers in motivating teacher work can be said to be good. Although it is still necessary to increase job performance and teacher job satisfaction which in the end will be able to increase the productivity of the work organization. The implication of this research is that a principal has broad insights and a good strategy to motivate teachers to teach